Contemplating the role of zinc-solubilizing bacteria in crop biofortification: An approach for sustainable bioeconomy - Upadhayay, Viabhav Kumar; Singh, Ajay Veer; Khan, Amir; Sharma, Adita (Frontiers in Agronomy, 2022)
Modern agriculture pays attention to improving agricultural production by producing zinc-enriched crops through zinc-solubilizing bacteria to strengthen the bioeconomy. Zinc deficiency in the soil reduces plant growth and also leads to less uptake of zinc in the edible portion of plants. Therefore, the zinc content in the edible parts of plants can be increased through the biofortification approach. However, most of the biofortification approaches are laborious and need expensive input in routine practices. Therefore, the microbiological biofortification approach may be beneficial in increasing the zinc concentration in plants and improving crop quality with the ultimate benefit of a greener path. The use of microbes may thus be favorable for elevating zinc content in plants and enhancing crop quality, ultimately providing a summation of the role of microorganisms for a greener strategy. In addition, the application of zinc-solubilizing bacteria as a potential biosource represents a cost-effective and alternate biofortification strategy. Zinc-solubilizing bacteria act as natural bio-fortifiers that can solubilize the unavailable form of zinc by secreting organic acids, siderophores, and other chelating compounds. This review thus focuses on zinc-solubilizing bacteria for plant biofortification and their contribution to enhance crop yield and the bioeconomy in a more sustainable manner.